(untitled) (Bangladesh Journal of Botany, 2023)
Three commercial Citrullus lanatus varieties, namely Sonya, Kanya and Sweet black-2, were investigated with cyto-molecular techniques for characterization. Despite having similar somatic chromosome numbers and karyotype formulae (2n = 22), these three varieties had considerable diversities in Chromomycin A3 (CMA)- and 4′, 6-diamidino-2-phenylindole (DAPI)-banding patterns. The total somatic chromosomal length was longest in Sweet black-2 (71.44 ± 2.94 µm) and shortest in Sonya (42.31 ± 2.45 µm). Each variety’s unique GC- and AT-rich chromatin composition was represented by a variety of numbers, percentages, and patterns of distribution. Eleven random primers were employed to evaluate the genetic diversity among three varieties. Each variety showed a distinct fingerprinting pattern with 88.72% polymorphism while having 10 of the same RAPD bands. Bangladesh J. Bot. 52(4): 1033-1040, 2023 (December)